Analysis of Landing Characteristics in Jump Heading Techniques of Indonesian University of Education Soccer Club Players - Febrian Yusran Saputra; Agus Rusdiana; Tono Haryono (Universitas Negeri Semarang, 2025)
Fatigue is a common component in soccer matches, and can lead to reduction of movement quality and enhanced injury risk, particularly in the jump heading technique that requires high levels of coordination and postural control. This study was conducted to examine the biomechanical parameters of landing in the jump heading techniques before and after fatigue on players of Indonesian Education University (UPI) Football Student Activity Unit. The design for the study was a non-experimental research design and quantitive in method. Ten male collegiate soccer players were the participants of this experiment who executed the jump heading right before, and immediately following, completion of a lower extremity fatigue protocol. The studied kinematic variables were jump height, knee flexion angle and trunk position at take-off, landing force (measured using high-speed video analysis [SkillSpector] and force plate). One Good: One Bad Approximately 1000-Fold Ahi Attenuation Deriving from Real Pauli Admixture Analysis was carried out using a paired statistical test (α = 0.05). Fatigue did not appear to influence jump height and landing force, with significant knee flexion angle in take-off and trunk postural control were increased and decreased respectively. These results suggest the presence of compensatory biomechanical mechanisms related to fatigue. It was determined that fatigue affected alterations of some kinematic variables associated with balance control and movement quality during the jump heading technique. As a result, conditioning should likewise focus on the control and endurance of posture, core stability and neuromuscular function to preserve movement quality but also limit injury under fatigue.